2019
DOI: 10.1038/s41598-019-51520-2
|View full text |Cite
|
Sign up to set email alerts
|

Jensen’s force and the statistical mechanics of cortical asynchronous states

Abstract: Cortical networks are shaped by the combined action of excitatory and inhibitory interactions. Among other important functions, inhibition solves the problem of the all-or-none type of response that comes about in purely excitatory networks, allowing the network to operate in regimes of moderate or low activity, between quiescent and saturated regimes. Here, we elucidate a noise-induced effect that we call “Jensen’s force” –stemming from the combined effect of excitation/inhibition balance and network sparsity… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 67 publications
1
5
0
Order By: Relevance
“…If stronger inhibition balances stronger excitation in a higher "tension" balance, we found that the dynamics are asynchronous and steady. Along with other recent studies [24, PLOS COMPUTATIONAL BIOLOGY [36][37][38], our findings suggest that the same cortical network could be tuned from criticality to asynchrony, by tuning inhibition and excitation appropriately.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…If stronger inhibition balances stronger excitation in a higher "tension" balance, we found that the dynamics are asynchronous and steady. Along with other recent studies [24, PLOS COMPUTATIONAL BIOLOGY [36][37][38], our findings suggest that the same cortical network could be tuned from criticality to asynchrony, by tuning inhibition and excitation appropriately.…”
Section: Discussionsupporting
confidence: 88%
“…Since stronger synapses are more effective for propagating activity, we suspect our work points to a different mechanism than that discussed by Priesemann and colleagues. Buendia et al focused on the 'low-activity intermediate' (LAI) regime, which had small fluctuations similar asynchronous regimes [37]. Their LAI regime emerged when they reduced the density of connections to a sufficiently sparse level (less than 0.01).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, while SOC provides a candidate framework for a unified theory of Consciousness (Melloni et al, 2021), a critical state is not strictly required for explaining the presence of spontaneous scale-free neuronal avalanches (e.g., Buendía et al, 2020aBuendía et al, , 2022. For example, it was suggested that during deep sleep or under anesthesia, the brain self-organizes at the edge of bistability (SOB, a first order phase transition Buendía et al, 2020b), rather than SOC (Priesemann et al, 2013). Furthermore, other bursting phenomena such as EEG micro states (Britz et al, 2009;Michel and Koenig, 2018) and neuronal assemblies (Papadimitriou et al, 2020) have been linked to cognition and perception.…”
Section: Discussionmentioning
confidence: 99%